Determine of Demographic Factor, Financial Literacy, And Internal Locus of Control on The Investment Decision Of Individual Investor - I Gede Adiputra Adiputra; Herman Ruslim; Rendy Sumadinata (Fakultas Ekonomi Universitas Negeri Manado, 2023)
The purpose of this study is to examine and analyze demographic factors, financial literacy, and locus of control in predicting investment decisions. Sampling in this study was carried out using a non-probability sampling method, namely purposive sampling, and data collection was carried out using a questionnaire. This study uses SmartPLS version 3.3.3 to process the collected data. This study uses panel data regression analysis with demographic factors, financial literacy and locus of control as independent variables and investment decisions as the dependent variable. This type of data uses secondary data derived from financial reports. The results of this study are that there is a significant influence of Demographic Factors, Financial Literacy, and Locus of Control on investment decisions on the Indonesia Stock Exchange.